2021
DOI: 10.1002/cncr.33327
|View full text |Cite
|
Sign up to set email alerts
|

Do all patients with cancer experience fatigue? A longitudinal study of fatigue trajectories in women with breast cancer

Abstract: BACKGROUND: Fatigue is a common and expected side effect of cancer treatment. However, the majority of studies to date have focused on average levels of fatigue, which may obscure important individual differences in the severity and course of fatigue over time. The current study was designed to identify distinct trajectories of fatigue from diagnosis into survivorship in a longitudinal study of women with early-stage breast cancer. METHODS: Women with stage 0 to stage IIIA breast cancer (270 women) were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 37 publications
7
31
0
Order By: Relevance
“… 15 Recently, the same authors identified consistent trajectories among 270 BC survivors, defining five fatigue groups: stable low (66%), stable high (13%), decreasing (4%), increasing (9%), and reactive (8%). 28 Our study confirms and expands on these previous studies. Particularly, our study calls for the implementation of several actions in the clinical care of patients with BC.…”
Section: Discussionsupporting
confidence: 91%
“… 15 Recently, the same authors identified consistent trajectories among 270 BC survivors, defining five fatigue groups: stable low (66%), stable high (13%), decreasing (4%), increasing (9%), and reactive (8%). 28 Our study confirms and expands on these previous studies. Particularly, our study calls for the implementation of several actions in the clinical care of patients with BC.…”
Section: Discussionsupporting
confidence: 91%
“…Anxiety and depression ranked as the first predictors of change in CRF, similar to the Fabi et al (2017) study, even though we shared different measuring periods. Our results indicating that depression remained higher than at initiation might be a potential risk of growing CRF after a single chemotherapy cycle echoed the observation from Bower et al (2021), that is, elevated depression and psychological distress would cause later CRF exacerbation.…”
Section: Discussionsupporting
confidence: 90%
“…Simultaneously, depression and anxiety accumulate gradually with the CRF (Oh & Cho, 2020). Additionally, more severe sleep disturbances and depression symptoms precipitate a higher risk of prolonged CRF (Bower et al, 2021). The factors mentioned above include neuromuscular fatigue as one of the distress symptoms; however, anxiety, depression, and sleep disturbance explained 56% of CRF variance (Chartogne et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…study) examining cancer-related fatigue (Bower et al, 2019(Bower et al, , 2020. Recruitment occurred between January 2013 and July 2015.…”
Section: Statement Of Relevancementioning
confidence: 99%